MEMBANGUN ORGANIZATIONAL AGILITY PADA LAM TEKNIK DALAM MENGHADAPI DINAMIKA PEST, SN DIKTI, DAN STANDAR INTERNASIONAL - Raden Danny Pranayudha (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
The Independent Accreditation Institute for Engineering Study Programs (LAM Teknik) operates in a highly dynamic environment, characterized by changes in national regulations (SN Dikti, Permendiktisaintek No. 39 of 2025) and global pressures (Washington Accord standards, etc.). This study analyzes strategies for building organizational agility to respond to these changes. Through a literature and qualitative study approach, it was found that organizational transformation requires a shift from mere administrative compliance to the development of purpose-based and skill-based capabilities. The discussion highlights the application of the "People Management Wheel" framework to manage dualistic tensions, the integration of "Green Human Resource Management (GHRM)" to strengthen organizational culture, and the adoption of "Entrepreneurial Leadership" to navigate uncertainty.